Evaluating How Landform Design and Soil Covers Influence Groundwater Recharge in a Reclaimed Watershed. Issue 8 (5th August 2019) - Lukenbach, M. C.; Spencer, C. J.; Mendoza, C. A.; Devito, K. J.; Landhäusser, S. M.; Carey, S. K.
Abstract: Landscape‐scale reconstruction and prescription of soil cover systems following oil sands mining is challenging due to the quality of available reclamation materials and the subhumid climate of the Boreal Plains of Canada. In an experimental reclaimed watershed (Sandhill Fen Watershed), basin‐scale upland landforms (i.e., hummocks) were designed to provide groundwater to adjacent lowlands, necessitating adequate recharge following establishment of forest vegetation. Volumetric water contents, soil water pressure heads, and groundwater levels were monitored for four years throughout the watershed and used to calibrate and verify numerical models in HYDRUS. Using a variably saturated two‐dimensional domain, we identified a threshold‐like relationship between recharge (or upflux) and upland hummock height, where upland hummocks not tall enough to limit root water uptake from the saturated zone decreased recharge or resulted in net upflux. Recharge varied with soil cover texture (higher in coarser‐textured) and associated soil hydraulic parameters. Furthermore, scenario tests indicated the importance and relative influence that maximum rooting depths, forest floor placement thicknesses, and leaf area indices (all associated with forest development) had on recharge. Simulations utilizing a historical climate record indicated that interannual climatic variability was as influential as variation in soil cover texture in determining recharge. Reclamation practitioners should recognize that the water balances of reconstructed landscapes are largely influenced by the trade‐off between optimizing forest productivity and sourcing water to downgradient landscape positions. Key Points: A tradeoff exists between optimizing forest productivity and facilitating groundwater recharge at reclaimed mines in sub‐humid regions Recharge exhibited a threshold‐like relationship to landform height, driven by the distance between the water table and rooting zone. Factors associated with forest development, such as maximum rooting depth, were key controls on recharge over the long‐term.